AGRICULTURAL CO-OPERATIVES: RESEARCHING MEMBERS PERCEPTION OF IMPORTANT ISSUES OF CO-OPERATIVES ON THE EXAMPLE OF SERBIA - N. Zaki; S. Vukoti; M. Laketa; L. Laketa (Journal of Animal and Plant Sciences, 2013)
This study is devoted to members’ perception of several important issues of co-operatives: leadership, members’ motivation, knowledge and skills and the role of the state. The research was conducted in Serbia and encompassed 228 members of 11 co-operatives. For the needs of the research a questionnaire with 1-5 response Likert-type scale was made. The hypotheses were proved by a chi-squared test and Pearson’s coefficient of linear correlation was used for the analysis of the connectivity of variables. The research has shown that according to the perception of the members of co- operatives leadership is necessary for a successful running a co-operative and co-operative development. Co-operative members would like to work closely with the co-operative and realize their income under equal market conditions through their co-operative. Furthermore, it is shown that appropriate knowledge and skills are needed for administrative and professional activities. The last researched issue according to members’ perception is that the co-operative system in Serbia is not adequate or sufficiently supported by the state.
Keywords: Agricultural co-operatives; co-operative member; leadership; members’ motivation; knowledge and skills; the role of state; Serbia